Cytomegalovirus immediate-early promoter efficiently drives heterogeneous gene expression in Spodoptera frugiperda (Sf9) insect cells - Li, S.; Zhang, Q. N.; Zhang, X. T.; Zheng, X. Y.; Lv, Y. F.; Hao, M. (Cellular and Molecular Biology, 2014)
Recently, wide attention has been given to the potential of recombinant baculovirus as a gene transfer vehicle for mammalian gene therapy. In this study, we packaged the recombinant baculoviruses with cytomegalovirus immediate-early (CMV-IE) promoter in Spodoptera frugiperda (Sf9) insect cells, and found that the CMV-IE promoter could efficiently drive the exogenic gene expression in the cells 12 h post-infection (h.p.i.). The expression level at 72 h.p.i. was only around half of that driven by polyhedrin promoter (Ppolh). However, the biological activity of the reporter proteins at 72 h.p.i. were similar with that driven by Ppolh. In addition, the Sf9 cells transfected with CMV-IE-containing plasmids also expressed foreign genes, suggesting that the CMV-IE-directed heterogeneous gene expression in the Sf9 cells was baculovirus-independent. These results demonstrate that the CMV-IE promoter might be used as a regular promoter in Sf9 cells.